2018
DOI: 10.1021/acsaem.8b00789
|View full text |Cite
|
Sign up to set email alerts
|

NH4+ Topotactic Insertion in Berlin Green: An Exceptionally Long-Cycling Cathode in Aqueous Ammonium-Ion Batteries

Abstract: Aqueous batteries represent promising solutions for large-scale energy storage considering the cost, safety, and performance. Despite the tremendous efforts devoted to the metal cations as charge carriers for batteries, scarce attention has been paid to the non-metal cations such as proton or ammonium. In this study, we report that a Berlin green framework exhibits much greater structural compatibility for NH4 + (de)­insertion than Na+ and K+. Ex situ structural studies reveal that the topochemistry of NH4 + i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
122
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(128 citation statements)
references
References 45 publications
6
122
0
Order By: Relevance
“…They also revealed that the NH 4 + intercalation/extraction in Berlin green was of nearly zero strain, thus resulting in enhanced cycling stability as compared with that of the Na + and K + intercalations. [ 119 ] Recently, Huang's group also reported the NH 4 + intercalation in Na‐FeHCF [ 120 ] and Cu‐HCF, [ 121 ] they not only achieved excellent cycling and rate performance via controlling morphologies and sizes of Na‐FeHCF nanocubes, but also revealed the selective NH 4 + channel in CuHCF, which leads to high cell voltage (≈1.8 V) and outstanding rate performance of Zn 2+ /NH 4 + hybrid batteries. In consideration of the high abundance of NH 4 + on earth, further investigations shall be done to develop effective PBA cathode materials for NH 4 + storage, which is of great importance for the development of next‐generation batteries.…”
Section: Prospects On Future Research and Development Of Pba Cathode mentioning
confidence: 99%
“…They also revealed that the NH 4 + intercalation/extraction in Berlin green was of nearly zero strain, thus resulting in enhanced cycling stability as compared with that of the Na + and K + intercalations. [ 119 ] Recently, Huang's group also reported the NH 4 + intercalation in Na‐FeHCF [ 120 ] and Cu‐HCF, [ 121 ] they not only achieved excellent cycling and rate performance via controlling morphologies and sizes of Na‐FeHCF nanocubes, but also revealed the selective NH 4 + channel in CuHCF, which leads to high cell voltage (≈1.8 V) and outstanding rate performance of Zn 2+ /NH 4 + hybrid batteries. In consideration of the high abundance of NH 4 + on earth, further investigations shall be done to develop effective PBA cathode materials for NH 4 + storage, which is of great importance for the development of next‐generation batteries.…”
Section: Prospects On Future Research and Development Of Pba Cathode mentioning
confidence: 99%
“…The dischargec apacities of Zn//Na-FeHCF ARAHBa re about 73. [7,13] After 400 cycles at 0.5 Ag À1 ,9 2% capacity retention with stable Coulombic efficiency at around 100 %i sa ttained (Figure S8). [7,13] After 400 cycles at 0.5 Ag À1 ,9 2% capacity retention with stable Coulombic efficiency at around 100 %i sa ttained (Figure S8).…”
mentioning
confidence: 98%
“…The dischargec apacities of Zn//Na-FeHCF ARAHBa re about 73.6, 67.4, 63, 60.8, 57.3, and 54.2 mAh g À1 (based on cathode'sa ctivem ass) at 0.25, 0.5, 0.75, 1, 1.5, and 2Ag À1 ,r espectively,s uggesting an excellent rate capability.I tp resents an outstanding capacity-recuperation performance with 98.3 % retention of its initial capacity as the current rate returns to 0.25 Ag À1 .I mpressively,t his ARAHB delivers ah igh discharge voltage of approximately 1.3 V ( Figure 2d), surpassing the value of the currently reported ammonium-ion batteries. [7,13] After 400 cycles at 0.5 Ag À1 ,9 2% capacity retention with stable Coulombic efficiency at around 100 %i sa ttained (Figure S8). Moreover, this ARAHB shows remarkablecycling stability with 92.1 %c apacity retention over 2000 cycles at ah igh current rate of 2Ag À1 .…”
mentioning
confidence: 98%
“…in 2012, [3] achievements have been made on NH 4 + storage for aqueous energy storage (Figure 1). Ti 3 C 2 MXene, [4] Prussian blue analogues (e.g., sodium iron hexacyanoferrate, [5] copper hexacyanoferrate, [6] berlin green, [7] ammonium Prussian white [2] ), organic solids (e.g., 3,4,9,10‐perylenetetracarboxylic diimide, [2] polyaniline [8] ), and metal oxides (e.g., titanic acid, [9] V 2 O 5 , [10] MoO 3 , [11] NH 4 V 4 O 10 [8] ) were studied to enrich the NH 4 + ‐storage chemistry. For example, Ji et al.…”
Section: Figurementioning
confidence: 99%